Trends in Plant-based Meat Alternatives (International Journal of Food and Nutritional Sciences, 2022)
The surge in demand for plant-based meat alternatives presents both opportunities andchallenges in the food industry. This paper introduces a novel approach, Plant-Based MeatAlternatives Using PBMA-DCNN (Deep Convolutional Neural Network), to address thesechallenges